Achievements, challenges and unmet needs for haemophilia patients with inhibitors: Report from a symposium in Paris, France on 20 November 2014. (5th January 2016) - Dargaud, Y.; Pavlova, A.; Lacroix‐Desmazes, S.; Fischer, K.; Soucie, M.; Claeyssens, S.; Scott, D.w.; d'Oiron, R.; Lavigne‐Lissalde, G.; Kenet, G.; Escuriola Ettingshausen, C.; Borel‐Derlon, A.; et al.
Summary: Over the past 20 years, there have been many advances in haemophilia treatment that have allowed patients to take greater control of their disease. However, the development of factor VIII (FVIII) inhibitors is the greatest complication of the disease and a challenge in the treatment of haemophilia making management of bleeding episodes difficult and surgical procedures very challenging. A meeting to discuss the unmet needs of haemophilia patients with inhibitors was held in Paris on 20 November 2014. Topics discussed were genetic and non‐genetic risk factors for the development of inhibitors, immunological aspects of inhibitor development, FVIII products and inhibitor development, generation and functional properties of engineered antigen‐specific T regulatory cells, suppression of immune responses to FVIII, prophylaxis in haemophilia patients with inhibitors, epitope mapping of FVIII inhibitors, current controversies in immune tolerance induction therapy, surgery in haemophilia patients with inhibitors and future perspectives for the treatment of haemophilia patients with inhibitors. A summary of the key points discussed is presented in this paper.